REFORMULASI DEFINISI ANAK SEBAGAI AHLI WARIS PENSIUNAN PEGAWAI NEGERI SIPIL - Ni Made Deby Anita Sari; I Nyoman Bagiastra; I Made Arya Utama (Jurnal Komunikasi Hukum, 2024)
Civil servants have the rights of protection, maintenance and welfare. Civil Servants pension security and Old Age Security are given as protection for the continuity of old-age income, as a right and as a reward for the service of civil servants given in the national social security program. When a civil servant dies, and the event that their widow/widower has also died, it will be given to his children. Thus, it can be seen that the heirs of retired civil servants who are entitled to civil servant insurance are limited to widows/widowers or their children. This writing aims to examine and resolve confusion arising from the ambiguity of the definition of children who are entitled to receive pension insurance from their parents who are retired civil servants when their parents have died. This study uses normative legal research methods to analyze the vague norms. The ambiguity of the definition of children in the law Number 11 of 1969 will cause problems in determining the position of children as heirs of pension rights for Civil Servants pensioners. After doing research, it is known that the position of adopted children is only entitled to an adopted child allowance. Meanwhile, children as recipients of the rights of pension are only legitimate biological children or legalized biological children.